IMPROVING THE ECOLOGICAL IMPACT OF SRENGSENG CITY FOREST IN JAKARTA: A COMPREHENSIVE EVALUATION - Eka Handayani; Qurrotu Aini Besila; Olivia Seanders (Universitas Trisakti, 2024)
The rapid urbanization in DKI Jakarta has led to environmental challenges such as air pollution, altered microclimates, and diminishing green open spaces (Ruang Terbuka Hijau - RTH). Urban forests, like Srengseng City Forest (Hutan Kota Srengseng) in West Jakarta, play a critical role in mitigating these ecological issues. This study evaluates the current condition of Srengseng City Forest, highlighting its potential and challenges in fulfilling its ecological functions. Through a combination of direct observation, documentation analysis, interviews, and literature review, this research identifies key areas for improvement in forest management and landscape design. Findings reveal that while Srengseng City Forest has significant potential to enhance urban ecological sustainability, it faces challenges in vegetation management, maintenance, and infrastructure. The study provides practical recommendations for optimizing the ecological function of the forest through sustainable landscape design and improved management practices, aiming to strengthen its contribution to Jakarta's environmental sustainability.